2002
DOI: 10.1088/0305-4470/35/10/303
|View full text |Cite
|
Sign up to set email alerts
|

A theorem on the absence of phase transitions in one-dimensional growth models with on-site periodic potentials

Abstract: We rigorously prove that a wide class of one-dimensional growth models with onsite periodic potential, such as the discrete sine-Gordon model, have no phase transition at any temperature T > 0. The proof relies on the spectral analysis of the transfer operator associated to the models. We show that this operator is Hilbert-Schmidt and that its maximum eigenvalue is an analytic function of temperature.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 20 publications
0
25
0
Order By: Relevance
“…Note that this does not imply that it must exhibit a phase transition: indeed, in [34] it was shown that a suitable change of variables casts the operator in a form compatible with the theorem, thus establishing the impossibility of phase transitions in this model (and in fact in a much wider class). Interestingly, the same problem arises in van Hove's theorem [8]; van Hove writes first his general transfer operator in a non-compact form, but he is able to rewrite it as a compact operator and to prove his theorem.…”
Section: Previous Examples Of Phase Transitions In the Context Of Thementioning
confidence: 99%
“…Note that this does not imply that it must exhibit a phase transition: indeed, in [34] it was shown that a suitable change of variables casts the operator in a form compatible with the theorem, thus establishing the impossibility of phase transitions in this model (and in fact in a much wider class). Interestingly, the same problem arises in van Hove's theorem [8]; van Hove writes first his general transfer operator in a non-compact form, but he is able to rewrite it as a compact operator and to prove his theorem.…”
Section: Previous Examples Of Phase Transitions In the Context Of Thementioning
confidence: 99%
“…Thus, in the combined high-temperature and high-density limit the PS model is amenable to an exact analytical treatment for any number of dimensions [26]. An interesting consequence of the boundedness of the PS potential in the 1D case is the plausible existence of a fluid-crystal phase transition [26], thus providing one of the rare examples of phase transitions in 1D systems [32]. In the complementary low-density domain, the cavity function y(r) has been recently determined to second order in density at any temperature [30].…”
Section: Introductionmentioning
confidence: 99%
“…A surprising consequence of the boundedness of the PS potential in the 1D case is the plausible existence of a fluid-crystal phase transition, 18 thus providing one of the rare examples of phase transitions in 1D systems. 21 Statistical mechanics has a long tradition of studying 1D systems, especially in those cases where an exact solution to the many-body problem has been found. 22 Of course, the 1D PS model does not intend to describe all the properties of real polymers in solution, for which spatial dimensionality is known to be important.…”
Section: Introductionmentioning
confidence: 99%